2020
DOI: 10.1016/j.wjam.2020.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the influence of the psychology changes of fear induced by the COVID-19 epidemic on the body

Abstract: In this paper, the theory of “Fear injury kidney” in traditional Chinese medicine is systematically reviewed, and it is found that long-term or excessive psychological changes of fear are likely to damage kidney qi and kidney essence. On this basis, the psychological studies of patients, medical staff and the public during the COVID-19 epidemic in China were analyzed, and fear psychology was found to be prevalent among all kinds of people. Modern researches on “Fear injury kidney” have a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…It is expected that the physical and psychological problems arising from COVID-19 fear will have a more significant impact on disadvantaged groups (Vieira et al 2020). High levels of COVID-19 fear can lead to negative psychological consequences in the individual and major medical illnesses by weakening and collapsing the immune system over time (Liu et al 2020). In the study, it was discovered the COVID-19 anxiety can increase depression, anxiety, and stress levels and, consequently, decrease the satisfaction with life of individuals, which is similar to the results of the current literature (Ahorsu et al 2020;Koçak et al 2021b;Satici et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…It is expected that the physical and psychological problems arising from COVID-19 fear will have a more significant impact on disadvantaged groups (Vieira et al 2020). High levels of COVID-19 fear can lead to negative psychological consequences in the individual and major medical illnesses by weakening and collapsing the immune system over time (Liu et al 2020). In the study, it was discovered the COVID-19 anxiety can increase depression, anxiety, and stress levels and, consequently, decrease the satisfaction with life of individuals, which is similar to the results of the current literature (Ahorsu et al 2020;Koçak et al 2021b;Satici et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…What this term means is to explain that there is a close relationship between the soul and the body. If the soul is in a normal state, such as trouble, worry, anxiety, and so on, then the body also suffers (Ramayulis, 2002;Qianwei et al, 2020).…”
Section: Relationship Between Islam and Mental Healthmentioning
confidence: 99%
“…Fear was prevalent among patients, healthcare workers and the public during the COVID-19 epidemic (Liu et al, 2020). Previous research has shown that fear of an epidemic affects psychological responses and behavior (Di Crosta et al, 2020).…”
Section: Fear Of Covid-19 and Mask-wearing Intentionsmentioning
confidence: 99%